The Neumann problem of Laplace's equation in semiconvex domains. (March 2016) - Yang, Sibei
Abstract: Let n ≥ 2 and Ω be a bounded semiconvex domain in R n . In this paper, we show that the Neumann problem for Laplace's equation in Ω with boundary data in L p ( ∂ Ω ) is uniquely solvable for p ∈ ( 1, ∞ ), which improves the well-known result for the Neumann problem.